Contributions of District Health Information Software 2 (DHIS2) to maternal and child health service performance in Ethiopia: an interrupted time series mixed-methods study - Taddese Alemu Zerfu; Moges Asressie; Amare Abera Tareke; Zenebu Begna; Tigist Habtamu; Netsanet Werkneh; Tariku Nigatu; Meskerem Jisso; Addisalem Genta (Archives of Public Health)
Abstract Background The District Health Information Software 2 (DHIS2) is the primary digital platform for health management information systems (HMIS) in Ethiopia, aligning with the nation’s digitization strategy. Despite widespread implementation, its effectiveness on key health service indicators, particularly maternal and child health (MCH) services, remain unclear. Objective This study aimed to evaluate the contribution of DHIS2 on data use and the performance of selected MCH indicators in Ethiopia, comparing data before and after the implementation of DHIS2. Methods We analysed data from primary health care units (PHUs) across five diverse regions of Ethiopia, encompassing urban, agrarian, and pastoralist settings. A mixed-methods approach was employed, combining quantitative and qualitative methods to provide a comprehensive understanding of the data. The quantitative component involved examining performance reports of selected maternal and child health (MCH) indicators from 2013 to 2022 to assess changes before and after the implementation of the District Health Information System 2 (DHIS2). Data were collected electronically and analysed using descriptive statistics and interrupted time series (ITS) analyses to identify trends and patterns. The qualitative component included interviews and focus group discussions with health workers and stakeholders to explore contextual factors influencing MCH service utilization and performance. The data were analysed thematically using OpenCode 4.1 software. Results The implementation of DHIS2 significantly contributed to the enhancement of MCH data utilization within PHU facilities. This improvement supported decision-making processes in various aspects of maternal and child healthcare delivery, including target setting, resource allocation, program monitoring, and clinical service provision. Specifically, DHIS2 led to increased monthly mean performance of key indicators such as antenatal care visits, skilled birth attendance, and immunization rates. Notable improvements in service delivery were observed, with significant increases in institutional delivery rates over time. Conclusions The study highlights DHIS2’s significant contribution to improving MCH services in Ethiopia, with increased institutional delivery rates and ANC coverage reflecting enhanced data-driven decision-making. Most facilities relied on DHIS2 for resource allocation and program monitoring, though challenges like offline usage and accessibility persist. To maximize impact, improving offline data management, training staff, leveraging real-time reporting, and addressing accessibility through connectivity investments are recommended.